A taula amb Pellegrino Artusi i Josep Pla: l'art de fer país a Itàlia i a Catalunya amb el que hem menjat. - CATTANEO, SIMONE (Scripta)
The purpose of this article is to show how the Italian Pellegrino Artusi (Forlimpopoli, 1820-Florence, 1911) and the Catalan Josep Pla (Palafrugell, 1897-Llofriu, 1981) used the art of cooking in their books La scienza in cucina e l'arte di mangiar bene (1891) and El que hem menjat (1972) to create a stronger sense of belonging and a more consistent idea of Italy and Catalonia in the population of their respective countries during some periods of political, social and cultural transition. On the one hand, they succeeded in doing it by recollecting and fixing a lot of gastronomic traditions to avoid their disappearance. On the other, they forged an enjoyable style and a modern language that reached a larger public and could be employed not only in the culinary field but also in everyday life.